Effect of Demographics on the Usage of Human Resource Information System - Motwani , Bharti (Gyan Management Journal, 2016)
Human Resource Information Systems (HR/SJ is an interacting system that generates and delivers functionality in order to automate HRM. HRIS is the system used to acquire, accumulate, injlue retrieve and distribute pertinent information regarding organization human services. Implemen an effective HRIS can surely deliver more effective and streamlined service. HRIS can assist hu resources in numerous ways particularly in day-to-day duties by streamlining workjlow proc through control processes, system interfaces and database validation. Despite the rapid adoptio HRIS in many organizations, researchers have argued that due to differences in the perceptio
Keywords: HRIS; HRM; Age; Gender; Qualification